Tax compliance intention behaviour among sole-proprietorships in Penang and its determinants - Noor Siti Aminah, Abd Weheed (2023)
Throughout the COVID-19 pandemic, the Malaysian government has consistently supported Small and Medium Enterprises (SMEs) by ensuring that they are resilient and growing. The 2021 Budget represents the largest allocation to date that benefits SMEs, totalling RM38.7 billion as incentives to SMEs for sustaining their businesses. Hence, SMEs have an obligation to support the government by voluntarily and accurately paying their taxes. SMEs are likely to have a variety of organisational structures, including sole proprietorships, partnerships, and limited liability companies. According to the literature, this group of taxpayers appears to be at a high risk of engaging in tax evasion and believes that paying taxes is a burden. Thus, this paper aims to focus on sole proprietorship, the small-scale sector known to be tough when it comes to paying taxes. The objective of this study is to examine the relationship between five independent variables; attitude, subjective norm, perceived behavioural control (probability of audit and licensed tax agent), and the dependent variable; intention to comply. The research framework of this study was developed based on five variables and employed the Theory of Planned Behaviour (TPB) which was developed by Ajzen (1991). Five hypotheses are tested based on the research framework. The research instrument for this study is a structured questionnaire. The questionnaires were distributed to taxpayers in Penang. A total of 135 samples were collected from taxpayers through simple random sampling techniques. According to the analysis, TPB is relevant to this study because it helps to explain how taxpayers behave in order to be aware of and obedient to tax. If taxpayers have strong intentions and beliefs, they will obey the tax. Taxpayers also think about the effects of their actions before acting in a particular way. Surprisingly, the findings ruled out the validity of audit probability in tax intention behaviour. This study contributes to the current literature by adding a new variable of the licensed tax agent to the tax compliance model. Next, the study addresses some limitations to the study in that the sample size that represents the whole population of individual business taxpayers in Penang may not be sufficient to generalise the whole Malaysian taxpayer population. Hence, the suggestion for future research is to increase the sample size so that future research can generalise the whole population and come out with a stronger regression model.